Carbonation and Phase Evolution in MgO-SiO2 Cements: Impact on Strength - Gonzalo Mármol; Ana Fernández-Jiménez; María-Teresa Blanco-Varela; Inés García-Lodeiro (Molecules)
Magnesium silicate hydrate (M-S-H) binders, synthesized from magnesia and silica, exhibit promising mechanical and thermal properties but face challenges in early strength development due to delayed kinetics and limited MgO solubility. This study investigates the impact of early exposure to CO2-saturated atmospheres on MgO-SiO2 cementitious systems, emphasizing the role of carbonation in phase evolution and mechanical performance. Early carbonation promotes the formation of hydrated magnesium hydroxycarbonates (HMHC), altering hydration pathways and reducing M-S-H gel content. Key analyses, including XRD, TGA, SEM-EDS, and FTIR, reveal that higher carbonation levels correlate with reduced Mg(OH)2 stability at early ages, an enhanced precipitation of HMHC phases, and significant effects on mineralogy and strength. Results underscore the influence of formulation, water-to-cement ratio, and early carbonation in optimizing strength and phase development, providing a pathway to more efficient MgO-SiO2 cement systems with reduced reliance on reactive SiO2.